2022
DOI: 10.30862/jri.v2i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Implications of cognitive abilities in students’ performance in physics using group dynamics and visual-clue strategies

Abstract: The study examined the implications of cognitive abilities of students on their academic performance when taught Physics using group dynamics and visual clue strategies. The quasi-experimental research design was adopted. The study population was 1,920 SSII students from 48 Secondary Schools in Makurdi metropolis from where the sample of 157 was drawn. The instruments: Physics Students’ Performance Test (PSPT) and Students’ Cognitive Ability Test (SCAT) were used for data collection. Hypotheses were tested at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Despite the importance attached to physics subject and effort of the government in ensuring that qualitative education is provided at the secondary level, this ugly incident of students' poor academic performance in physics subject still lingers on in Obi Local Government Area of Benue State. It has been observed that students often perform poorly in the subject (Achor, Danjuma & Orji, 2018;Achor & Ngbea, 2022). This poor performance may be due to anxiety particularly during examination.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Despite the importance attached to physics subject and effort of the government in ensuring that qualitative education is provided at the secondary level, this ugly incident of students' poor academic performance in physics subject still lingers on in Obi Local Government Area of Benue State. It has been observed that students often perform poorly in the subject (Achor, Danjuma & Orji, 2018;Achor & Ngbea, 2022). This poor performance may be due to anxiety particularly during examination.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Emotional intelligence (EI) is an important part of the learning process to realize the expected learning achievement. Learning is no longer just a process of transferring knowledge or learning materials to students (Achor & Ngbea, 2022;Nusantari et al, 2021;Obielodan et al, 2021;Rumalolas et al, 2021). Learning has a wider place, and it must be a vehicle for the holistic development of students' potential through the active role of students toward better change (Mbaubedari et al, 2022;Pambudi et al, 2022;Soltura, 2022;Vargas-Hernández & Vargas-González, 2022;Zannah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, contemporary constructivist educational theory emphasizes problem-solving, critical thinking, authentic learning experiences, literacy, communication skill, and collaboration -pedagogical practices that transform the teacher's role from information disseminator to learning facilitator, assisting students in actively engaging with information and materials to construct their own understandings. Thus, students learn not just what to study, but also how to learn (Achor & Ngbea, 2022;Lowenthal & Muth, 2008;Vargas-Hernández & Vargas-González, 2022).…”
Section: Introductionmentioning
confidence: 99%